Quantum chemical rovibrational analysis of aminoborane and its isotopologues. Issue 3 (18th May 2022) - Schneider, Moritz; Rauhut, Guntram
Abstract: Aminoborane, H2 NBH2 and its isotopologues, H2 N 10 BH2, D2 NBD2, and D2 N 10 BD2, have been studied by high‐level ab initio methods. All calculations rely on multidimensional potential energy surfaces and dipole moment surfaces including high‐order mode coupling terms, which have been obtained from electronic structure calculations at the level of explicitly correlated coupled‐cluster theory, CCSD(T)‐F12, or the distinguishable cluster approximation, DCSD. Subsequent vibrational structure calculations based on second‐order vibrational perturbation theory, VPT2, and vibrational configuration interaction theory, VCI, were used to determine rotational constants, centrifugal distortion constants, vibrationally averaged geometrical parameters and (an)harmonic vibrational frequencies. The impact of core‐correlation effects is discussed in detail. Rovibrational VCI calculations were used to simulate the gas phase spectra of these species and an in‐depth analysis of the ν 7 band of aminoborane is provided. Color‐coding is used to reveal the identity of the individual progressions of the rovibrational transitions for this particular mode. Abstract : The rovibrational spectrum of aminoborane has been investigated by high‐level ab initio methods based on a multidimensional potential energy surface obtained from explicitly correlated coupled‐cluster calculations.